EFFECT OF RATE AND FREQUENCY OF MICRONUTRIENT ON GROWTH ATTRIBUTES AND DRY MATTER YIELD OF BANANA CV. GRAND NAINE UNDER SOUTH GUJARAT CONDITION - NARENDRA SINGH; SONAL TRIPATHI; PATEL V. A.; JAIMIN NAIK; CHAUHAN ADITI (The Bioscan, 2020)
The field experiment was carried out using banana as a plant crop and ratoon crop at Soil and Water Management Research Unit, NAU, Navsari. The different rate of multi-micronutrients mixture grade-V (M 1 =25g/plant, M 2 = 50g/plant, M 3 = 75g/plant) and the frequency of application (S 1 = Basal and S 2 = 50 per cent each as basal and 50 per cent two month after planting) was used in different treatment. The treatments viz., PFDC(T 1 ), PFDC+M 1 S 1 (T 2 ), PFDC+M 1 S 2 (T 3 ), PFDC+M 2 S 1 (T 4 ), PFDC+M 2 S 2 (T 5 ), PFDC+M 3 S 1 (T 6 ), PFDC+M 3 S 2 (T 7 ) and 100% RDF only (T 8 ) for both years were tested using RBD with four replications. The dry matter yield (t ha 1 ) of different banana plant part (leaves, pseudostem and fruits) was significantly more (2.18, 10.43 and 10.70 t ha -1 respectively) in treatment T 7 i.e. (M 3 S 2 ) compared to rest of the treatments. Whereas the growth parameters (plant height, pseudostem girth and number of functional leaves) were non-significantly influenced. Similar result was observed in ratoon crop. Application of treatment T 6 (T 1 + M 3 S 1 ) and T 7 (T 1 + M 3 S 2 ) can be beneficial under south Gujarat condition to achieve a good growth attributes and dry matter yield different plant parts.